ANALISIS PENYELESAIAN SENGKETA PEMUTUSAN HUBUNGAN KERJA OLEH PENGADILAN NEGERI MANADO (STUDI PUTUSAN NO.2 /PDT.SUS- PHI/2020/PN.MND): Analysis Settlement of Employment Termination Dispute By The Manado Industrial Relations Court (Study Of Decision Number 2/PDT.SUS-PHI/2020/PN.MND) - Pangemanan, Anatasya Maranata; Pamungkas, Yogo (AMICUS CURIAE, 2024)
Work Relations aren’t always good, disputes often arise which known as Industrial Relations Disputes. Best Effort to resolve this dispute is both parties carry out negotiations, Law Number 2 of 2004 concerning Settlement of Industrial Relations Disputes (“UUPPHI”) requires that industrial relations disputes first step to resolve is through Bipartite Negotiation. This research was conducted to discuss whether the procedures to resolve employment termination disputes between parties are in accordance to UUPPHI and whether the decision of Manado Industrial Relations Court Number 2/Pdt.Sus-PHI/2020/PN.Mnd is in accordance to UUPPHI. In answering these problems, this research was carried out using Normative Law research method, which is analytically descriptive, and base on primary, secondary and tertiary data which is analyzed qualitatively so that conclusions can be drawn deductively. Based on the research results, conclusion that can be drawn was this dispute resolution process between partied aren’t through bipartite negotiation, so the dispute resolution process weren’t in accordance to applicable laws and regulations. Panel of judges in handling down decision was also not in accordance to UUPPHI, where the panel of judges should not have accepted the registered lawsuit or at least handed down the Niet Onvankelijke Verklaard decision.